TUTURAN TINDAKAN KOMUNIKATIF SUBJEK DIRI DALAM WACANA NARASI - Heri Suwignyo (Bahasa dan Seni: Jurnal Bahasa, Sastra, Seni, dan Pengajarannya, 2012)
Putting self-autonomy of a man as the rational subject itself is an extreme while putting a dependency of rational human subject within themselves in relation to psychological, socio-economic is the other extreme. This study aims at explaining how  the  main  character,  Minke  in  the  narrative  discourse  address  these  two extremes.  The  data  in this  research  were  in the  form  of  text  units  which  were analyzed using Buhler semiotic model. The results of the study showed that there are three ways used by the subjects to express themselves, namely (1) symptomic way, which was expressed through the validity claims of honesty; (2) the signalic way, shown through the regulative speech using normative validity of accuracy; and (3) the symbolic way, done through the objective validity of truth claims.The findings imply that the subject’s  orientations  in doing communicative  speech acts are the achievement of self-understanding and rational agreement without violence.